Contribuição para o conhecimento fitoquímico da espécie Vismia guianensis (Hypericaceae). - Souza, Maria Sallett Rocha (2014)
Vismia guianensis (Hypericaceae) is popularly known in Brazil as lacre or goma-lacre. In the present work the extraction of chemicals from the leaves of V. guianensis by maceration with ethanol. The phytochemical screening showed the presence of flavonoids, saponins, steroids, tannins and anthraquinones. By column chromatography were isolated Stigmasterol, β-Sitosterol and Vismiaquinone A from the hexane phase, and Kaempferol from the ethyl acetate phase. The structures were elucidated using nuclear magnetic resonance 1H and 13C unidimensional and bidimensional. Of the inflorescences of V. guianensis, was performed extraction of essential oil by steam drag in Clevenger apparatus, and parallel soxhlet extraction with hexane, ethyl acetate and methanol solvents. The determination of the constituents of the essential oil was performed by gas chromatography coupled to a mass spectrometer (GC/MS) and antimicrobial activity was evaluated against Staphylococcus aureus, Pseudomonas aeruginosa, Escherichia coli, and was determined by minimum inhibitory concentration (MIC), activity was considered significant in these bacterial cultures